Dip-coated HNR120 photoresists thin-film optical waveguides - Singh, Ghanshyam K.; Low, Andy L.Y.; Seng Yong, Yik (2005)
We report on our systematic and detailed study of fabrication and characterization of HNR120 photoresists thin-film optical waveguides. Various waveguide properties, such as refractive index, optical losses as a function of temperature, waveguide thickness, dispersion and birefringence have been studied. The optical loss are found to be < 1.4 dB cm(-1). © 2005 Elsevier GmbH. All rights reserved.